A Comprehensive Account of Synthesis and Biological Activities of α‐lidene‐ Benzocycloalkanones and Benzoheterocycles. Issue 33 (1st September 2022) - Chowdhury, Moumita Ghosh; Das, Rudradip; Vyas, Het; Sasane, Tejal; Mori, Omprakash; Kamble, Sayali; Patel, Sagarkumar; Shard, Amit
Abstract: α‐lidene‐benzocycloalkanones or benzene‐fused cycloalkanones are a significant moiety in medicinal chemistry. Drug development using these moieties can explore the pharmacophoric space owing to their sp 2 and sp 3 hybridization, highly flexible bicyclic structure, and varied ring diameters. In addition, it imparts a more significant contribution based on stereochemistry and pliability in the three‐dimensional space. The α‐lidene‐benzocycloalkanone series is a challenging target as it has multiple reactive sites, such as the bicyclic benzo‐annulated center, the reactive carbonyl fragment, and the partly hydrogenated ring of varying sizes. This domain lacks discussion and organized material, and this review can fill that gap, focusing on medicinally essential moieties like tetralone, indanone, and suberine. In addition, this review discusses α‐lidene‐benzoheterocycles that are promising in the field of drug development. Due to their stereogenecity and target selectivity, most research and applications focus on unstrained 5 and 6‐membered rings, such as α‐lidene‐benzocyclopentanones, α‐lidene‐benzocyclohexanones, α‐lidene‐benzofurano‐3‐ones, α‐lidene‐benzopyrano‐3‐ones, and α‐lidene‐indolin‐3‐ones. This review shall also aid medicinal chemists in determining the optimal technique for developing novel benzene fused heterocycles or carbocycles with various biological activities. Abstract : This review provides the succinct procedures for synthesizing α‐lidene‐ benzocycloalkanones and benzoheterocycles. It also includes several newly developed techniques for the catalyst‐free synthesis of α‐lidene‐benzocycloalkanones and benzoheterocycles.Additionally, it offers the reported schemes and methods, allowing for a thorough and improved knowledge of the protocols. Further, the review will help medicinal chemists choose the best method for creating novel benzene‐fused heterocycles or carbocycles with various biological activities. Finally, the conclusion and perspective are also mentioned, and the review contributes to fully comprehending the subject.